1993
DOI: 10.2337/diacare.16.2.434
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Other Risk Factors, and 12-Yr Cardiovascular Mortality for Men Screened in the Multiple Risk Factor Intervention Trial

Abstract: These findings emphasize the importance of rigorous sustained intervention in people with diabetes to control blood pressure, lower serum cholesterol, and abolish cigarette smoking, and the importance of considering nutritional-hygienic approaches on a mass scale to prevent diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

69
1,977
9
129

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,644 publications
(2,184 citation statements)
references
References 42 publications
69
1,977
9
129
Order By: Relevance
“…Several studies have recently assessed the relationship between type 2 diabetes and the risk of stroke. Type 2 diabetes has been shown to be an independent risk factor for stroke morbidity [15,[18][19][20][21][22] and mortality [14,16,17,22,40]. The Renfrew and Paisley Study found that type 2 diabetes was a predictor of stroke incidence among women but not among men [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have recently assessed the relationship between type 2 diabetes and the risk of stroke. Type 2 diabetes has been shown to be an independent risk factor for stroke morbidity [15,[18][19][20][21][22] and mortality [14,16,17,22,40]. The Renfrew and Paisley Study found that type 2 diabetes was a predictor of stroke incidence among women but not among men [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies have assessed the independent effect of type 2 diabetes on stroke risk, with inconsistent results. Some [14][15][16][17][18][19][20][21][22], but not all studies [23,24], have identified type 2 diabetes as an independent risk factor for stroke. Moreover, it is not fully understood whether the risk of stroke death associated with incident diabetes is similar to that associated with incident stroke.…”
mentioning
confidence: 99%
“…2,3 Epidemiological analyses of United Kingdom Prospective Diabetes Study data from newly-diagnosed T2DM identified higher low-density lipoprotein cholesterol, lower highdensity lipoprotein cholesterol, hyperglycemia, hypertension, and smoking as potentially modifiable cardiovascular risk factors. 4 However, even after adjustment for these factors, people with T2DM remain at double the cardiovascular risk as those without T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that patients with type 2 diabetes have an increased risk of cardiovascular disease (CVD) [1]. Several independent risk markers for the development of CVD in patients with diabetes have been identified, e.g., hyperglycaemia, hypertension, hypercholesterolaemia, smoking and microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%